Fahrenheit 451. - Derviş Durmaz (Türk Kütüphaneciliği, 2013)
Published in 1951, the famous science-fiction novel depicts an oppressive future society where books are burnt by firemen, people watch brain-washing shows on TV and those in possession of books are annihilated. The book’s title refers to the fact that paper ignites at 451 degrees Fahrenheit. The novel was also made into a film in 1966 by the French film- maker François Truffaut.